Inter- and intra-species interactions between meat plant environmental bacteria and a non-biofilm-forming Escherichia coli O157:H7 strain in co-culture biofilms - Visvalingam, Jeyachchandran; Zhang, Peipei; Yang, Xianqin (Frontiers in Microbiology, 2025)
This study evaluated the impact of meat-processing environmental bacteria (MPB) on biofilm formation by Escherichia coli O157:H7 in dual-species cultures. Biofilm development by 50 MPB and E. coli O157:H7 was assessed using crystal violet staining. Four MPB and E. coli O157:H7 combinations were evaluated further for viable cell numbers. A chlorinated alkaline agent and a quaternary ammonium-based agent were evaluated for their ability to remove biofilms. The E. coli O157:H7 strain was a non-biofilm former. In dual-species biofilms, if the companion MPB did not produce detectable biofilm, then the pairing did not produce measurable biofilms either. The interaction effect between MPB and E. coli O157:H7 was predominantly no-effect (neutral). Among the four MPB isolates tested by viable cell enumeration method, only generic E. coli genotype 136 reduced viable numbers of E. coli O157:H7 in dual-strain biofilm. Sequential treatment with cleaning and sanitizing treatment provided a better removal of biofilm than a single-agent treatment.